Family empowerment in protecting children from the influence of addictive substances during COVID-19 pandemic in village of Bandar Labuhan district of Tanjung Morawa regency of Deli Serdang - Nasution, Eva Syahfitri; Dalimunthe, Ritha F; Pujiati; Siregar, Ameilia Zuliyanti; Hutagalung, Arif Qaedi (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2020)
The Covid-19 pandemic that occurred shows the increasingly important role of families in caring and educating children. Amount of children spend time at home because studying online, it means that they spend a lot of time outside with friends. This allows children to consume addictive substances. From the initial survey conducted in village of Bandar Labuhan district of Tanjung Morawa regency of Deli Serdang, it was found that children secretly consume addictive substances which are harmful to their own health, such as smoking. The method of implementing community service activities is carried out in three stages, including the stages of preparation, implementation and guidance. Addictive substances are substances that cause addiction or dependence and are harmful. From the results of the dedication, it was found that most of the abuse of addictive substances in children in village of Bandar Labuhan district of Tanjung Morawa was cigarettes, glue and gasoline. Most of the factors that influence addictive substance abuse in children are curiosity. Empowerment of families in protecting children from addictive substance abuse is very necessary for children avoid addictive substances. This is in accordance with the mandate of Law No. 35 of 2014 concerning Amendments to Law No. 23 of 2002 concerning Child Protection and North Sumatra Regional Regulation No. 1 of 2019 concerning Facilitation for the Prevention of Abuse of Narcotics, Psychotropics and Other Addictive Substances.